Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Chika Mulya Multimedia - Sukmo Nugroho Pahlefi; Sigit Purwanto; Mohammad Jibriel Avessina (CV. ITTC INDONESIA, 2025)
This study aims to determine the influence of leadership style and work motivation on employee performance at PT. Chika Mulya Multimedia with a sample of 60 respondents used. The method used is a quantitative approach by distributing questionnaire research instruments to employees, then processed using a competitor application, namely SPPS. This research was carried out at PT. Chika Mulya Multimedia with the variables of leadership style (X1) and work motivation (X2) on employee performance (Y) was processed using correlation analysis, regression analysis, t-test, F-test and determination coefficient. The results of this study used a t-test (partial) which showed that the leadership style variable had a partial effect on employee performance and work motivation had a partial effect on employee performance. Meanwhile, the F test (simultaneous) shows that work motivation and work discipline on employee performance simultaneously or together affect employee performance at PT. Chika Mulya Multimedia.